The Gene Analysis and Probiotic Potential Characterization of Pseudomonas alcaligenes SG03 - Manguntungi, Baso; Rusmana, Iman; Mustopa, Apon Zaenal; Meryandini, Anja (Bogor Agricultural University, Indonesia, 2025)
AHPND causes up to 80% of shrimp mortality, severely impacting Indonesia's aquaculture. Rising antibiotic resistance necessitates sustainable alternatives. This study investigates the probiotic potential of Pseudomonas alcaligenes SG03, a bacterium with unique genomic traits, to address antibiotic resistance and promote animal health. Genome analysis revealed a 6.17 Mb genome with 4,446 protein clusters, including genes for carbohydrate metabolism (26.63%), amino acid metabolism (19.93%), and energy metabolism (10.88%). Key probiotic-related genes, such as acid resistance (rpoS, actP), salinity tolerance (gshA, cysK), antibiotic resistance (vanB, gyrA), and metal resistance (copZ, zwf), were identified. In vitro, assays evaluated probiotic properties under conditions mimicking the shrimp gastrointestinal tract. Osmo-tolerance tests showed optimal growth at 10% glucose, with a significant drop in viability at higher concentrations. Autoaggregation increased progressively, reaching 0.78 at 18 hours and 0.13 at 48 hours. Optimal growth occurred at 30°C, with a 2.5-fold increase in optical density compared to 25°C. NaCl tolerance peaked at 2% (20.33×1012 CFU at 48 hours), while bile salt tolerance was highest at 0.1% (27.00×1012 CFU at 48 hours). pH tolerance was optimal at pH 5 (20.00×1012 CFU at 48 hours). Antioxidant (53.00%) and anti-inflammatory (60.33%) activities peaked after 48 hours. Phenotypic antibiotic resistance was observed against Tetracycline, Amoxicillin, Cefixime, Streptomycin, and Chloramphenicol, with proteolytic activity but no lipolytic or hemolytic properties. These findings highlight P. alcaligenes SG03’s potential as a probiotic in aquaculture to support shrimp health and reduce antibiotic dependency. Future studies should focus on in vivo validation and formulation development.